Experimental and theoretical understanding on electrochemical activation and inactivation processes of Nb3O7(OH) for ambient electrosynthesis of NH3. Issue 28 (3rd July 2019) - Wu, Tianxing; Han, Miaomiao; Zhu, Xiaoguang; Wang, Guozhong; Zhang, Yunxia; Zhang, Haimin; Zhao, Huijun
Abstract : Our experimental and theoretical calculation results revealed the electrochemical activation and inactivation processes of ultrafine Nb3 O7 (OH) nanoparticle catalysts for electrocatalytic N2 reduction to produce NH3 under ambient conditions. Abstract : Deeply understanding the electrochemical activation and inactivation processes of an electrocatalyst is critically important for establishing a high-efficiency nitrogen reduction reaction (NRR) to synthesize an NH3 system. Here we report the utilization of a facile vapor-phase hydrothermal (VPH) method to directly grow ultrafine Nb3 O7 (OH) nanoparticles on commercial carbon fiber cloth (Nb3 O7 (OH)/CFC) for the NRR. The results demonstrate that the Nb3 O7 (OH)/CFC can afford an average NH3 yield rate of 622 μg h −1 mgcat. −1 with a high faradaic efficiency (FE) of 39.9% at −0.4 V versus the reversible hydrogen electrode (RHE) in 0.1 M Na2 SO4 electrolyte (pH = 6.1) within 30 min of the NRR, surpassing the performance of most recently reported aqueous-based NRR electrocatalysts. The experimental and theoretical calculation results reveal that the in situ electrochemically converted NbO from Nb3 O7 (OH) during the NRR is the catalytic active phase with a N2 adsorption free energy of −0.97 eV; however with a reaction time over 30 min, the generated active *N atoms in the *N–NH3 → *N + NH3 hydrogenation step during the NRR are thermodynamically favourable for binding to the oxygen vacancies of NbO to form oxygen-containing NbN0.64 with reduced N2 adsorption free energy (−0.32 eV), resulting in significantly decreased NRR activity. Our studies suggest that although NbO possesses high NRR activity, it may not be a suitable NRR electrocatalyst, owing to easy formation of low active niobium oxynitride during the NRR.